Sensitive monitoring of penicillin antibiotics in milk and honey treated by stir bar sorptive extraction based on monolith and LC‐electrospray MS detection. Issue 5 (4th February 2013) - Huang, Xiaojia; Chen, Linli; Chen, Meng; Yuan, Dongxing; Nong, Shuyu
<x xml:space="preserve">Abstract</x> In the present study, a convenient and sensitive method for determination of six penicillin antibiotics (amoxicillin, ampicillin, penicillin G, oxacillin, cloxacillin, and dicloxacillin) in milk and honey samples was developed. Milk and honey samples were diluted with water, then directly treated by stir bar sorptive extraction based on poly (vinylimidazole‐divinylbenzene) monolithic material as coating. The analytes were analyzed by LC/ESI‐ MS/MS. Several extraction parameters including extraction and desorption time, pH value, and ionic strength in sample matrix were investigated in detail. Under the optimized extraction conditions, the calculated detection limits for the target compounds were as low as 0.23–2.66 ng/kg in milk and 0.18–1.42 ng/kg in honey, respectively. Good linearity was obtained for analytes with the correlation coefficients (R2) above 0.997. Excellent method reproducibility was achieved in terms of intraday and interday precisions, indicated by the RSDs of <5.0 and <10.0%, respectively. Finally, the proposed method was successfully applied to the determination of penicillin antibiotics residues in different milk and honey samples.